DIFFERENTIAL EXPRESSION OF MICRORNA IN GENERALIZED ANXIETY DISORDER AND ITS ASSOCIATION WITH SOCIAL SUPPORT - Kong, Lingming; Zhu, Xiaoli; Niu, Wei; Zhang, Liyi (International Journal of Research -GRANTHAALAYAH, 2021)
To explore the differential expression of microRNA (miRNA, miR-) and its correlation with social support and personality in Generalized Anxiety Disorder (GAD) patients. A total of 80 GAD patients and 80 control participants were selected from our serial study samples to be tested for microarray analysis, and real time quantitative Polymerase Chain Reaction (qRT-PCR) verification was carried out in both patient group and control group. Correlation between miRNA expression and social support were also carried out. According to microarray analysis, 6 miRNAs were differentially expressed between patient group and control group, with miR-4505, miR-4484, miR-4674, miR-501-3p and miR-663 up-regulated, and miR-1301 down-regulated; qPCR verification revealed that 5 miRNAs (miR-1301, miR-4484, miR-4674, miR-501-3p, miR-663, miR-4505) were significantly up-regulated and the expression of miRNA-1301 down-regulated; the expression of miRNA-1301 was significantly related to social support in GAD patients. In conclusions, comprehensive factors, including miRNA regulation, social support may be involved into the aetiology of GAD.